Manajemen Kompetensi Profesional Guru Pendidikan Jasmani Sekolah Menengah Atas (SMA) - Soedjono Soedjono; I Made Sudana; Ibnu Fatkhu Royana (Journal of Physical Activity and Sports (JPAS), 2023)
The purpose of this study is to examine the level of professionalism of high school teachers in Semarang City. The research method used is qualitative with the type of case study. Data collection techniques used observation, interview, and document study. The research samples were principals, MGMP leaders, and physical education teachers who met the criteria for selecting informants. The results showed that the level of professionalism of physical education teachers in Semarang cannot be said to be high, this is because there are many problems that affect the level of professionalism of physical education teachers in Semarang City, such as inadequate facilities and infrastructure, teachers still teach using the demonstration method, and weak teacher administration. The conclusion of this study is that physical education teachers, especially in Semarang City, should further improve their competence both in teaching and administration so that they can have an impact on students.